Backwards Anaphora and Backwards Ellipsis in Slovenian Multi-Clause Sentences - Gabrovšek, Dejan (Slovenski jezik / Slovene Linguistic Studies, 2024)
The article discusses backwards anaphora and backwards ellipsis in Slovenian multi-clause sentences. It demonstrates their characteristics on all types of Slovenian multi-clause sentences that allow the two phenomena. It turns out that backwards anaphora and backwards ellipsis are rare; backwards anaphora in the role of correlative is the most frequent, and backwards anaphora in coordination is the rarest. I have found individual instances of backwards anaphora and backwards ellipsis even in relationships where they were not envisaged in most studies to date. Backwards anaphora and backwards ellipsis can also have a stylistic effect. It is also possible to have more than one backwards anaphora or backwards ellipsis in one sentence. A semi-backwards anaphora and semi-backwards ellipsis are also shown as a special type of a backwards anaphora and backwards ellipsis.